Self-checking color-changing fault warning wire
Patent Information
- Application Number
- CN202611478812.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
然而,热致变色材料直接加入聚合物基体时,还需要兼顾材料加工温度、变色材料的分散稳定性以及导线绝缘性能;同时,聚合物基体自身热传递能力较低,热量由导线内部向热致变色材料传递时容易产生一定的响应滞后
本申请中采用乙烯-醋酸乙烯酯共聚物作为变色警示层基体,使变色警示层具有较低的加工温度和较好的柔韧性;含环氧基的乙烯-丙烯酸酯共聚物能够改善温敏释放不可逆显色微胶囊及表面改性球形氧化铝在聚合物基体中的润湿和分散状态,表面改性球形氧化铝则有利于降低聚合物基体内部的局部热传递阻力,使导线局部产生的热量较快传递至温敏释放不可逆显色微胶囊,使变色警示层在保持加工稳定性和柔韧性的同时提高热响应效率,并通过不可逆颜色变化对导线曾发生的局部过热进行持久警示;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the technical field of warning wires, and in particular to a self-testing color-changing fault warning wire. Background Technology
[0002] As power line load levels continue to increase, factors such as loose conductor joints, increased contact resistance, abnormal overload, and aging insulation materials can easily cause localized temperature rises. If localized overheating is not detected in time, it may further lead to decreased insulation performance, conductor damage, or even line faults. Currently, the detection of conductor overheating mainly relies on manual inspection, infrared thermometers, or temperature-indicating patches placed at specific locations. These methods typically require external equipment or additional detection components, making it difficult to continuously and intuitively identify localized overheating that has occurred at any point along the conductor. This is especially true for intermittent overheating faults, which are more likely to be missed after the temperature returns to normal during inspections.
[0003] To improve the fault warning capability of conductors, existing technologies have incorporated thermochromic materials into the conductor insulation layer or sheath, allowing for color changes as the conductor temperature rises. However, when thermochromic materials are directly added to the polymer matrix, it is necessary to consider the material processing temperature, the dispersion stability of the thermochromic material, and the conductor insulation performance. Furthermore, the polymer matrix itself has low thermal conductivity, and heat transfer from the conductor interior to the thermochromic material can easily result in a certain response lag. Simply increasing the amount of inorganic thermally conductive filler may lead to problems such as increased system viscosity, uneven dispersion of thermochromic microcapsules, and decreased material flexibility.
[0004] Therefore, how to improve the thermal response efficiency of irreversible thermochromic materials in polymer matrices while maintaining the insulation performance and processing stability of the conductor, so that the conductor can quickly generate and retain a clearly visible color warning after local overheating, is a technical problem that still needs to be solved in this field. Summary of the Invention
[0005] In order to improve the thermal response efficiency of irreversible thermochromic materials while maintaining the insulation performance and processing stability of the conductor, this application provides a self-testing color-changing fault warning conductor.
[0006] Firstly, this application provides a self-testing color-changing fault warning wire, which adopts the following technical solution: A self-testing color-changing fault warning wire includes a conductive core and, from the inside out, a polyethylene insulation layer, a color-changing warning layer, and a transparent protective layer disposed on the outside of the conductive core. The raw material of the color-changing warning layer includes the following components in parts by weight: 60-72 parts of ethylene-vinyl acetate copolymer, 5-10 parts of epoxy-containing ethylene-acrylate copolymer, 10-18 parts of thermosensitive release irreversible color-developing microcapsules, 5-20 parts of surface-modified spherical alumina, 0.2-0.5 parts of antioxidant, and 0.2-0.8 parts of lubricating and dispersing agent.
[0007] By adopting the above technical solution, using ethylene-vinyl acetate copolymer as the matrix of the color-changing warning layer, the color-changing warning layer has a lower processing temperature and better flexibility. The epoxy-containing ethylene-acrylate copolymer can improve the wetting and dispersion state of the thermosensitive release irreversible color-developing microcapsules and surface-modified spherical alumina in the polymer matrix. The surface-modified spherical alumina is beneficial to reduce the local heat transfer resistance inside the polymer matrix, so that the heat generated locally in the wire can be transferred to the thermosensitive release irreversible color-developing microcapsules more quickly. This allows the color-changing warning layer to improve thermal response efficiency while maintaining processing stability and flexibility, and provides a lasting warning of local overheating that has occurred in the wire through irreversible color change.
[0008] In one specific feasible implementation, the method for preparing the thermosensitive release irreversible chromogenic microcapsules includes the following steps: An azo oil-soluble dye is added to n-hexadecane and stirred at 50–70°C until dissolved to obtain a dyed alkane indicator solution; the dyed alkane indicator solution, isocyanate prepolymer, and ethyl acetate are mixed to obtain an oil phase; Polyvinyl alcohol was added to deionized water to prepare an aqueous phase, and the oil phase was added to the aqueous phase. The mixture was emulsified at 3000-6000 rpm for 5-15 min to obtain an oil-in-water emulsion with an average droplet size of 5-15 μm. The oil-in-water emulsion is heated to 50-70°C, and water-soluble polyol and polyurethane reaction catalyst are added. The reaction is carried out at 300-600 rpm for 2-5 hours, so that the isocyanate prepolymer and water-soluble polyol polymerize at the oil-water interface and form a polyurethane-based shell. After the reaction was completed, the mixture was cooled, filtered, washed with deionized water, and vacuum dried at 40–60 °C to obtain thermosensitive release irreversible colorimetric microcapsules.
[0009] By adopting the above technical solution, water-in-oil droplets of a specific particle size are formed through emulsification, and a polyurethane-based shell is formed by reacting isocyanate prepolymer with water-soluble polyol at the oil-water interface. This allows the dyed alkane indicator liquid to be encapsulated inside microcapsules. The polyurethane shell can isolate the indicator liquid during storage and normal use, reducing its migration and leakage. At the same time, by controlling the emulsification rate, reaction temperature, and time, microcapsules with more uniform particle size are obtained, which is beneficial to their stable dispersion in the color-changing warning layer.
[0010] In one specific implementation scheme, the weight ratio of the azo oil-soluble dye, n-hexadecane, isocyanate prepolymer, ethyl acetate, polyvinyl alcohol, deionized water, water-soluble polyol, and polyurethane reaction catalyst is (0.5-1.5):(25-35):(6-12):(10-20):(1-3):(80-120):(3-8):(0.02-0.08).
[0011] In one specific implementation, the method for preparing the surface-modified spherical alumina includes the following steps: Spherical alumina with a D50 of 0.5–2.5 μm was dried at 100–120 °C for 2–4 h and then added to an ethanol-water mixed solvent and ultrasonically dispersed for 20–40 min to obtain a spherical alumina dispersion. γ-aminopropyltriethoxysilane was added to an ethanol-water mixed solvent, and the pH was adjusted to 4.0-5.0 with acetic acid. The mixture was stirred and hydrolyzed at 20-30°C for 20-60 min to obtain a silane hydrolysate. The silane hydrolysate was added to the spherical alumina dispersion and reacted at 60–75°C and 300–500 rpm for 2–5 h to form a silane-modified layer on the surface of the spherical alumina with γ-aminopropyltriethoxysilane. After the reaction is complete, the mixture is filtered, washed 2-3 times with anhydrous ethanol, dried under vacuum at 70-80℃ for 4-12 hours, pulverized and depolymerized to obtain surface-modified spherical alumina.
[0012] By adopting the above technical solution, micron-sized spherical alumina is dried and dispersed, and γ-aminopropyltriethoxysilane pre-hydrolyzed under acidic conditions forms a silane-modified layer on the surface of the alumina. This reduces the tendency of alumina particles to agglomerate, improves its interfacial compatibility with the organic polymer matrix, and enables the spherical alumina to be more uniformly dispersed in the color-changing warning layer, thus improving local heat transfer while maintaining electrical insulation properties.
[0013] In one specific implementation, the weight ratio of the spherical alumina to γ-aminopropyltriethoxysilane is 100:(1-3).
[0014] In one specific implementation, the raw materials of the polyethylene insulation layer include linear low-density polyethylene and low-density polyethylene, and the mass ratio is (65-80):(20-35).
[0015] By adopting the above technical solution, an insulation layer is formed by compounding linear low-density polyethylene with low-density polyethylene. The linear low-density polyethylene is beneficial to improving mechanical strength and resistance to environmental stress cracking, while the low-density polyethylene is beneficial to improving melt processability and flexibility. The two work together to enable the polyethylene insulation layer to take into account electrical insulation performance, mechanical properties and extrusion processing stability.
[0016] In one specific implementation, the raw materials of the transparent protective layer include the following components in parts by weight: 65-80 parts of aliphatic polyurethane acrylate oligomer, 15-30 parts of acrylate reactive diluent, 1-4 parts of photoinitiator, 0.5-2 parts of ultraviolet absorber, 0.2-1 parts of hindered amine light stabilizer, and 0.3-1.5 parts of surface-modified nano silica.
[0017] By adopting the above technical solution, the aliphatic polyurethane acrylate system can form a transparent, flexible and wear-resistant protective layer after photocuring; the ultraviolet absorber reduces the entry of ultraviolet rays into the color-changing warning layer, the hindered amine light stabilizer inhibits the photo-oxidative aging of the protective layer, and the surface-modified nano silica improves the wear resistance and scratch resistance. Therefore, while maintaining visible light transmittance, the weather resistance of the transparent protective layer is improved, thereby reducing the impact of the outdoor environment on the color recognition and long-term stability of the color-changing warning layer.
[0018] Secondly, this application provides a method for preparing a self-testing color-changing fault warning wire, which adopts the following technical solution: A method for preparing a self-testing color-changing fault warning wire includes the following steps: S1. A polyethylene insulation layer is formed by extruding a conductive wire core, which is then cooled and shaped before being cross-linked by electron beam irradiation and cooled again. S2. Ethylene-vinyl acetate copolymer, epoxy-containing ethylene-acrylate copolymer, thermosensitive release irreversible color-developing microcapsules, surface-modified spherical alumina, antioxidant, lubricating and dispersing agent are mixed, replasticized and formed on the outside of polyethylene insulation layer to obtain color-changing warning layer. S3. A transparent protective layer is set outside the color-changing warning layer to obtain a self-testing color-changing fault warning wire.
[0019] By adopting the above technical solution, a polyethylene insulation layer is first formed, followed by a color-changing warning layer containing temperature-sensitive release irreversible color-developing microcapsules and surface-modified spherical alumina, and finally a transparent protective layer is set. This allows the insulation, overheat warning, and environmental protection functions to be undertaken by different layers, avoiding the direct addition of a large number of functional components to the polyethylene main insulation layer and affecting its insulation performance. It also helps to ensure that the color-changing warning layer can be visually identified directly through the transparent protective layer.
[0020] In one specific implementation, the highest processing temperature of the color-changing warning layer in step S2 is at least 15°C lower than the thermal response temperature of the thermosensitive release irreversible color-developing microcapsule.
[0021] By adopting the above technical solution, the maximum processing temperature of the color-changing warning layer is controlled at least 15°C lower than the thermal response temperature of the temperature-sensitive release irreversible color-developing microcapsules. This can create a sufficient safety margin for processing temperature, reduce the premature irreversible color change or failure of microcapsules during mixing and molding, and ensure that the microcapsules maintain effective temperature response capability when local overheating occurs during actual operation of the conductor.
[0022] In summary, this application includes at least one of the following beneficial technical effects: In this application, ethylene-vinyl acetate copolymer is used as the matrix of the color-changing warning layer, which gives the color-changing warning layer a lower processing temperature and better flexibility. The epoxy-containing ethylene-acrylate copolymer can improve the wetting and dispersion state of the thermosensitive release irreversible color-developing microcapsules and surface-modified spherical alumina in the polymer matrix. The surface-modified spherical alumina is beneficial to reduce the local heat transfer resistance inside the polymer matrix, so that the heat generated locally in the wire can be transferred to the thermosensitive release irreversible color-developing microcapsules more quickly. This allows the color-changing warning layer to improve thermal response efficiency while maintaining processing stability and flexibility, and to provide a lasting warning of local overheating that has occurred in the wire through irreversible color change. In this application, linear low-density polyethylene and low-density polyethylene are blended to form an insulation layer. The linear low-density polyethylene is beneficial to improving mechanical strength and resistance to environmental stress cracking, while the low-density polyethylene is beneficial to improving melt processability and flexibility. The two work together to enable the polyethylene insulation layer to take into account electrical insulation performance, mechanical properties and extrusion processing stability. The method in this application first forms a polyethylene insulation layer, then forms a color-changing warning layer containing temperature-sensitive release irreversible color-developing microcapsules and surface-modified spherical alumina, and finally sets a transparent protective layer. This allows the insulation, overheat warning, and environmental protection functions to be undertaken by different layers, avoiding the direct addition of a large number of functional components to the polyethylene main insulation layer and affecting its insulation performance. It also helps to ensure that the color-changing warning layer can be visually identified directly through the transparent protective layer. Detailed Implementation
[0023] The present application will be further described in detail below with reference to the embodiments.
[0024] All raw materials used in the examples are commercially available. The linear low-density polyethylene used is SABIC® LLDPE324CE; the low-density polyethylene used is SABIC® LDPE HP2022NN; the ethylene-vinyl acetate copolymer used is SKFunctional Polymer's EVATANE® 28-05; the epoxy-containing ethylene-acrylate copolymer used is SKFunctional Polymer's LOTADER® AX8900; the antioxidant used is Irganox® 1010; the lubricating and dispersing agent used is ethylene bis-stearamide; the azo oil-soluble dye has CAS number 85-83-6; the isocyanate prepolymer used is Covestro's Desmodur® E 30700; the water-soluble polyol used is polyethylene glycol 400; the polyurethane reaction catalyst used is triethylenediamine; the aliphatic polyurethane acrylate oligomer used is Allnex's EBECRYL® 8402; the acrylate reactive diluent used is 1,6-hexanediol diacrylate; and the photoinitiator used is Omnirad® 1173; UV absorber: Tinuvin® 384-2; hindered amine light stabilizer: Tinuvin® 123; surface-modified nano-silica: AEROSIL® R 972; conductive core: commercially available Class 2 stranded bare copper conductor conforming to GB / T 3956, with a nominal cross-sectional area of 10 mm². 2 . Preparation Example
[0025] Preparation Example 1 Preparation Example 1 provides a method for preparing thermosensitive release irreversible chromogenic microcapsules, comprising the following steps: Take 0.5 parts of azo oil-soluble dye and 25 parts of n-hexadecane, stir at 50°C until the azo oil-soluble dye is completely dissolved to obtain a dyeing alkane indicator solution; add 6 parts of isocyanate prepolymer and 10 parts of ethyl acetate, stir evenly to obtain the oil phase; Take 1 part of polyvinyl alcohol and add it to 80 parts of deionized water. Stir until completely dissolved to obtain an aqueous phase. Slowly add the oil phase to the aqueous phase and emulsify at 3000 rpm for 15 min to obtain an oil-in-water emulsion with an average droplet size of 5-15 μm. The oil-in-water emulsion was heated to 50°C, and 3 parts of water-soluble polyol and 0.02 parts of polyurethane reaction catalyst were added. The mixture was reacted at 300 rpm for 5 hours to allow the isocyanate prepolymer to react with the water-soluble polyol at the oil-water interface to form a polyurethane-based shell. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and vacuum dried at 40°C for 12 hours to obtain thermosensitive release irreversible colorimetric microcapsules.
[0026] Preparation Example 2 Preparation Example 2 provides a method for preparing thermosensitive release irreversible chromogenic microcapsules, comprising the following steps: Take 1 part of azo oil-soluble dye and 30 parts of n-hexadecane, stir at 60°C until the azo oil-soluble dye is completely dissolved to obtain a dyeing alkane indicator solution; add 9 parts of isocyanate prepolymer and 15 parts of ethyl acetate, stir evenly to obtain the oil phase; Take 2 parts of polyvinyl alcohol and add it to 100 parts of deionized water. Stir until completely dissolved to obtain an aqueous phase. Slowly add the oil phase to the aqueous phase and emulsify at 4500 rpm for 10 min to obtain an oil-in-water emulsion with an average droplet size of 5-15 μm. The oil-in-water emulsion was heated to 60°C, and 5 parts of water-soluble polyol and 0.05 parts of polyurethane reaction catalyst were added. The mixture was reacted at 450 rpm for 3.5 h to allow the isocyanate prepolymer to react with the water-soluble polyol at the oil-water interface to form a polyurethane-based shell. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 50°C for 10 hours to obtain thermosensitive release irreversible colorimetric microcapsules.
[0027] Preparation Example 3 Preparation Example 3 provides a method for preparing thermosensitive release irreversible chromogenic microcapsules, comprising the following steps: Take 1.5 parts of azo oil-soluble dye and 35 parts of n-hexadecane, stir at 70°C until the azo oil-soluble dye is completely dissolved to obtain a dyeing alkane indicator solution; add 12 parts of isocyanate prepolymer and 20 parts of ethyl acetate, stir evenly to obtain the oil phase; Take 3 parts of polyvinyl alcohol and add it to 120 parts of deionized water. Stir until completely dissolved to obtain an aqueous phase. Slowly add the oil phase to the aqueous phase and emulsify at 6000 rpm for 5 min to obtain an oil-in-water emulsion with an average droplet size of 5-15 μm. The oil-in-water emulsion was heated to 70°C, and 8 parts of water-soluble polyol and 0.08 parts of polyurethane reaction catalyst were added. The mixture was reacted at 600 rpm for 2 hours to allow the isocyanate prepolymer to react with the water-soluble polyol at the oil-water interface to form a polyurethane-based shell. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 60°C for 8 hours to obtain thermosensitive release irreversible colorimetric microcapsules.
[0028] Preparation Example 4 Preparation Example 4 provides a method for preparing surface-modified spherical alumina, comprising the following steps: Take 100 parts of spherical alumina with a D50 of 0.5 μm, dry at 100℃ for 4 h, add to an ethanol-water mixed solvent consisting of 150 parts of anhydrous ethanol and 10 parts of deionized water, and ultrasonically disperse for 40 min to obtain a spherical alumina dispersion. Take 1 part of γ-aminopropyltriethoxysilane and add it to an ethanol-water mixed solvent consisting of 50 parts of anhydrous ethanol and 5 parts of deionized water. Add glacial acetic acid to adjust the pH value to 4.5 and stir at 20℃ for 60 min to hydrolyze and obtain silane hydrolysate. The silane hydrolysate was slowly added to the spherical alumina dispersion and reacted at 60℃ and 300rpm for 5h to form a silane-modified layer on the surface of the spherical alumina with γ-aminopropyltriethoxysilane. After the reaction was completed, the mixture was filtered, washed three times with anhydrous ethanol, dried under vacuum at 70°C for 12 hours, and then pulverized and depolymerized to obtain surface-modified spherical alumina.
[0029] Preparation Example 5 Preparation Example 5 provides a method for preparing surface-modified spherical alumina, comprising the following steps: Take 100 parts of spherical alumina with a D50 of 1.5 μm, dry at 110℃ for 3 h, add to an ethanol-water mixed solvent consisting of 200 parts of anhydrous ethanol and 20 parts of deionized water, and ultrasonically disperse for 30 min to obtain spherical alumina dispersion. Take 2 parts of γ-aminopropyltriethoxysilane and add it to an ethanol-water mixed solvent consisting of 60 parts of anhydrous ethanol and 10 parts of deionized water. Add glacial acetic acid to adjust the pH value to 4.5 and stir at 25°C for 40 min to hydrolyze and obtain silane hydrolysate. The silane hydrolysate was slowly added to the spherical alumina dispersion and reacted at 68℃ and 400rpm for 3.5h to form a silane-modified layer on the surface of the spherical alumina with γ-aminopropyltriethoxysilane. After the reaction was completed, the mixture was filtered, washed three times with anhydrous ethanol, dried under vacuum at 75°C for 8 hours, and then pulverized and depolymerized to obtain surface-modified spherical alumina.
[0030] Preparation Example 6 Preparation Example 6 provides a method for preparing surface-modified spherical alumina, comprising the following steps: Take 100 parts of spherical alumina with a D50 of 2.5 μm, dry at 120℃ for 2 h, add to an ethanol-water mixed solvent consisting of 250 parts of anhydrous ethanol and 30 parts of deionized water, and ultrasonically disperse for 20 min to obtain a spherical alumina dispersion. Take 3 parts of γ-aminopropyltriethoxysilane and add it to an ethanol-water mixed solvent consisting of 80 parts of anhydrous ethanol and 15 parts of deionized water. Add glacial acetic acid to adjust the pH value to 4.5 and stir at 30℃ for 20 min to hydrolyze and obtain silane hydrolysate. The silane hydrolysate was slowly added to the spherical alumina dispersion and reacted at 75℃ and 500rpm for 2 hours to form a silane-modified layer on the surface of the spherical alumina with γ-aminopropyltriethoxysilane. After the reaction was completed, the mixture was filtered, washed three times with anhydrous ethanol, dried under vacuum at 80°C for 4 hours, and then pulverized and depolymerized to obtain surface-modified spherical alumina. Example
[0031] Example 1 Example 1 provides a self-testing color-changing fault warning wire.
[0032] A self-testing color-changing fault warning wire includes a conductive core and, from the inside out, a polyethylene insulation layer, a color-changing warning layer, and a transparent protective layer disposed on the outside of the conductive core.
[0033] Example 1 also provides a method for preparing a self-testing color-changing fault warning wire, including the following steps: S1. Take 65 parts of linear low-density polyethylene, 35 parts of low-density polyethylene, 0.3 parts of antioxidant and 0.5 parts of polyethylene wax and mix them evenly. After being melted and plasticized by a single screw extruder, the mixture is coated on the outside of the conductive wire core. The temperature of each zone of the extruder is set to 130℃, 145℃, 155℃ and 160℃ respectively, and the die head temperature is 160℃. After water cooling and shaping, a polyethylene insulation layer with a thickness of 1.0 mm is formed. Then, the polyethylene insulation layer is irradiated and crosslinked by electron beam with an electron beam absorbed dose of 120 kGy. S2. Take 5 parts of epoxy-containing ethylene-acrylate copolymer and 5 parts of surface-modified spherical alumina premix obtained in Preparation Example 4, then add 60 parts of ethylene-vinyl acetate copolymer, 0.2 parts of antioxidant and 0.2 parts of lubricating dispersant, and mix and plasticize at 80-90°C; after the polymer matrix is mixed evenly, add 10 parts of thermosensitive release irreversible color-developing microcapsules obtained in Preparation Example 1, and continue to mix evenly; the resulting mixture is coated onto the outside of the polyethylene insulation layer through a low-temperature single-screw extruder, with the extruder temperature zones set to 75°C, 82°C, 88°C and 92°C respectively, and the die head temperature set to 92°C, forming a color-changing warning layer with a thickness of 0.30 mm; S3. Take 65 parts of aliphatic polyurethane acrylate oligomer, 15 parts of acrylate reactive diluent, 0.5 parts of UV absorber, 0.2 parts of hindered amine light stabilizer, and 0.3 parts of surface-modified nano-silica, mix and disperse them evenly, then add 1 part of photoinitiator. After vacuum degassing for 10 minutes, coat the mixture evenly onto the outer surface of the color-changing warning layer and cure it with ultraviolet light at an energy of 1000 mJ / cm². 2 During the curing process, the surface temperature of the conductor is controlled to not exceed 45℃, forming a transparent protective layer with a thickness of 0.20mm, resulting in a self-testing color-changing fault warning conductor.
[0034] Example 2 The difference between Example 2 and Example 1 is that, in S1, 72 parts of linear low-density polyethylene, 28 parts of low-density polyethylene, 0.3 parts of antioxidant and 0.5 parts of polyethylene wax are mixed evenly and then melted and plasticized in a single-screw extruder and coated on the outside of the conductive wire core. The temperatures of each zone of the extruder are set to 130°C, 145°C, 155°C and 160°C in sequence, and the die head temperature is 160°C. After water cooling and shaping, a polyethylene insulation layer with a thickness of 1.0 mm is formed. Subsequently, the polyethylene insulation layer is irradiated and crosslinked using an electron beam with an electron beam absorbed dose of 120 kGy. S2. Take 8 parts of epoxy-containing ethylene-acrylate copolymer and 12 parts of surface-modified spherical alumina premix obtained in Preparation Example 4, then add 66 parts of ethylene-vinyl acetate copolymer, 0.35 parts of antioxidant and 0.5 parts of lubricating dispersant, and mix and plasticize at 85°C; after the polymer matrix is mixed evenly, add 15 parts of thermosensitive release irreversible color-developing microcapsules obtained in Preparation Example 1, and continue to mix evenly; the resulting mixture is coated onto the outside of the polyethylene insulation layer through a low-temperature single-screw extruder, with the extruder temperature zones set to 75°C, 85°C, 90°C and 95°C respectively, and the die head temperature set to 95°C, forming a color-changing warning layer with a thickness of 0.30 mm; S3. Take 72 parts of aliphatic polyurethane acrylate oligomer, 22 parts of acrylate reactive diluent, 1.0 part of UV absorber, 0.6 parts of hindered amine light stabilizer, and 0.8 parts of surface-modified nano-silica, mix and disperse them evenly, then add 2.5 parts of photoinitiator. After vacuum degassing for 10 minutes, coat the mixture evenly onto the outer surface of the color-changing warning layer and cure it with ultraviolet light at an energy of 1000 mJ / cm². 2 During the curing process, the surface temperature of the conductor is controlled to not exceed 45°C, forming a transparent protective layer with a thickness of 0.20 mm, resulting in a self-testing color-changing fault warning conductor; the remaining steps are consistent with Example 1.
[0035] Example 3 The difference between Example 3 and Example 1 is that, in S1, 80 parts of linear low-density polyethylene, 20 parts of low-density polyethylene, 0.3 parts of antioxidant and 0.5 parts of polyethylene wax are mixed evenly and then melted and plasticized in a single-screw extruder and coated on the outside of the conductive wire core. The temperatures of each zone of the extruder are set to 130°C, 145°C, 155°C and 160°C in sequence, and the die head temperature is 160°C. After water cooling and shaping, a polyethylene insulation layer with a thickness of 1.0 mm is formed. Subsequently, the polyethylene insulation layer is irradiated and crosslinked using an electron beam with an electron beam absorbed dose of 120 kGy. S2. Take 10 parts of epoxy-containing ethylene-acrylate copolymer and 20 parts of surface-modified spherical alumina premix obtained in Preparation Example 4, then add 72 parts of ethylene-vinyl acetate copolymer, 0.5 parts of antioxidant and 0.8 parts of lubricating and dispersing agent, and mix and plasticize at 85-90°C; after the polymer matrix is mixed evenly, add 18 parts of thermosensitive release irreversible color-developing microcapsules obtained in Preparation Example 1, and continue to mix evenly; the resulting mixture is coated onto the outside of the polyethylene insulation layer through a low-temperature single-screw extruder, with the extruder temperature zones set to 78°C, 86°C, 92°C and 98°C respectively, and the die head temperature set to 98°C, forming a color-changing warning layer with a thickness of 0.30 mm; S3. Take 80 parts of aliphatic polyurethane acrylate oligomer, 30 parts of acrylate reactive diluent, 2 parts of UV absorber, 1 part of hindered amine light stabilizer, and 1.5 parts of surface-modified nano-silica, mix and disperse them evenly, then add 4 parts of photoinitiator. After vacuum degassing for 10 minutes, coat the mixture evenly onto the outer surface of the color-changing warning layer and cure it with ultraviolet light at an energy of 1000 mJ / cm². 2 During the curing process, the surface temperature of the conductor is controlled to not exceed 45°C, forming a transparent protective layer with a thickness of 0.20 mm, resulting in a self-testing color-changing fault warning conductor; the remaining steps are consistent with Example 1.
[0036] Example 4 The difference between Example 4 and Example 2 is that, in S2, the same mass of the surface-modified spherical alumina obtained in Preparation Example 5 is used; the remaining steps are the same as in Example 2.
[0037] Example 5 The difference between Example 5 and Example 2 is that, in S2, the same mass of the surface-modified spherical alumina obtained in Preparation Example 6 is used; the remaining steps are the same as in Example 2.
[0038] Example 6 The difference between Example 6 and Example 4 is that, in S2, an equal mass of the thermosensitive release irreversible colorimetric microcapsules obtained in Preparation Example 2 is used; the remaining steps are the same as in Example 4.
[0039] Example 7 The difference between Example 7 and Example 4 is that, in S2, an equal mass of the thermosensitive release irreversible colorimetric microcapsules obtained in Preparation Example 3 is used; the remaining steps are the same as in Example 4.
[0040] Example 8 The difference between Example 8 and Example 6 is that in S1, 100 parts of linear low-density polyethylene, 0.3 parts of antioxidant and 0.5 parts of polyethylene wax are mixed evenly; the remaining steps are the same as in Example 6.
[0041] Example 9 The difference between Example 9 and Example 6 is that in S1, 100 parts of low-density polyethylene, 0.3 parts of antioxidant and 0.5 parts of polyethylene wax are mixed evenly; the remaining steps are the same as in Example 6. Comparative Example
[0042] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in S2, 5 parts of epoxy-containing ethylene-acrylate copolymer are not added, and 5 parts of ethylene-vinyl acetate copolymer are used as an equal substitute, that is, the amount of ethylene-vinyl acetate copolymer is adjusted from 60 parts to 65 parts; the remaining steps are the same as in Example 1.
[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in S2, 5 parts of the surface-modified spherical alumina obtained in Preparation Example 4 are not added, and 5 parts of ethylene-vinyl acetate copolymer are used as an equal substitute, that is, the amount of ethylene-vinyl acetate copolymer is adjusted from 60 parts to 65 parts; the remaining steps are the same as in Example 1.
[0044] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in S2, 5 parts of epoxy-containing ethylene-acrylate copolymer were replaced with 5 parts of epoxy-free ethylene-acrylate copolymer; the remaining steps were the same as in Example 1. Performance testing experiment
[0045] Unless otherwise specified, five parallel samples were set up for each group, and the arithmetic mean was taken as the test result. Before the test, the samples were placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24 hours to acclimate them.
[0046] Color change response time: Referring to GB / T 3979-2008 "Methods for Measuring the Color of Objects" and GB / T 7921-2008 "Uniform Color Space and Color Difference Formula", three-layer composite sheets of polyethylene insulation layer / color change warning layer / transparent protective layer were prepared simultaneously according to the same raw material composition and processing conditions as in each embodiment and comparative example. The L*, a*, and b* values of the outer transparent protective layer surface of the sample before heating were measured using a spectrophotometer, and these were used as the initial color data. The test conditions used a D65 standard illuminator and a 10° standard colorimetric observer. The constant temperature heating stage was preheated to 120±1℃, ensuring full contact between the polyethylene insulation layer side of the sample and the heating stage to simulate the process of heat transfer from the inside to the outside after the conductor heats up. Simultaneously, a non-contact spectrophotometer was used to continuously measure the color of the outer surface of the transparent protective layer, recording the L*, a*, and b* values every 5 seconds.
[0047] The overall color difference ΔE of the sample during heating relative to its initial state was calculated using the CIELAB color difference formula. When ΔE first reaches 5.0, the sample is considered to have produced a clear and identifiable color change. The time elapsed from the sample's initial contact with the 120°C heating stage until ΔE first reaches 5.0 is recorded as the color change response time, measured in seconds. A shorter color change response time indicates a faster thermal response speed of the color-changing warning layer after localized overheating of the conductor.
[0048] ΔE after color change: Using the color change response time test method described above, after the sample undergoes a significant color change, it is heated at 120±1℃ for 5 minutes to allow the color to stabilize. The sample is then removed and cooled at 23±2℃ for 10 minutes. The L*, a*, and b* values of the sample after color change are determined according to GB / T 3979-2008, and the CIELAB comprehensive color difference ΔE between the sample after color change and the sample before heating is calculated according to GB / T 7921-2008. The larger the ΔE, the more obvious the color difference before and after overheating, and the higher the visual recognition of the fault warning.
[0049] ΔE retention rate after 24 hours of cooling: After the color change test, the sample was placed at 23±2℃, relative humidity 50±5%, and in the dark for another 24 hours. The L*, a*, and b* values were measured again, and the overall color difference ΔE24 after 24 hours was calculated. The ΔE retention rate after 24 hours of cooling was calculated according to the following formula: ΔE retention rate = ΔE24 / ΔE0 × 100%; where ΔE0 is the overall color difference of the sample after heating to 120℃ and cooling for 10 minutes; ΔE24 is the overall color difference of the sample after being placed at room temperature for 24 hours. The higher the ΔE retention rate, the less likely the color produced after overheating is to recover, and the stronger the ability of the conductor to continuously mark historical overheating faults.
[0050] Interlayer peel strength: Referring to GB / T 2791-1995 "Test Method for T-Peel Strength of Adhesives - Flexible Materials to Flexible Materials", a three-layer composite sheet of polyethylene insulation layer / color-changing warning layer / transparent protective layer was prepared simultaneously according to the same raw material composition and processing conditions as in the examples and comparative examples, and cut into strips with a width of 25 mm. During the preparation process, a 50 mm long unbonded area was reserved at one end of the polyethylene insulation layer and the color-changing warning layer as a clamping end. The polyethylene insulation layer and the color-changing warning layer were clamped at one end in the upper and lower clamps of a universal testing machine, respectively, and T-shaped peeling was performed at 23±2℃ and a speed of 100 mm / min. The average peel force in the stable peeling stage was recorded and normalized with the sample width to calculate the interlayer peel strength, in N / mm. The higher the interlayer peel strength, the more stable the interfacial bonding between the polyethylene insulation layer and the color-changing warning layer.
[0051] Tensile strength: Referring to GB / T 2951.11-2008, three-layer composite sheets of polyethylene insulation layer / color-changing warning layer / transparent protective layer were prepared simultaneously according to the same raw material composition, layer thickness, and processing conditions as in the embodiments and comparative examples. Dumbbell-shaped specimens were prepared according to GB / T2951.11-2008. After conditioning the specimens in an environment of 23±2℃ and 50±5% relative humidity for 24 hours, tensile tests were performed using a universal testing machine at a tensile speed of 250 mm / min. The maximum tensile load before specimen fracture was recorded, and the tensile strength was calculated based on the initial effective cross-sectional area of the specimen, in MPa.
[0052] Table 1 Performance test results of the conductor
[0053] Combining Example 1 with Comparative Examples 1-3, Comparative Example 1, without the addition of epoxy-containing ethylene-acrylate copolymer, showed an extended color change response time from 78 s to 96 s, a decrease in ΔE after color change from 29.1 to 23.9, a decrease in interlayer peel strength from 1.56 N / mm to 0.83 N / mm, and a decrease in tensile strength. This indicates that epoxy-containing ethylene-acrylate copolymer can improve the interfacial compatibility and dispersion state between thermosensitive release irreversible color-developing microcapsules and surface-modified spherical alumina and the EVA matrix, thereby helping to reduce interfacial heat transfer resistance and improve color change. The bonding stability between the warning layer and the polyethylene insulation layer; Comparative Example 2, without the addition of surface-modified spherical alumina, had a significantly prolonged color change response time of 121s, the longest among all groups of samples, while the decrease in ΔE and ΔE retention rate after color change was relatively small, and the interlayer peel strength and tensile strength remained at a high level; This indicates that the main role of surface-modified spherical alumina is not simply to improve mechanical strength or color development, but to significantly shorten the overheat warning response time by reducing the local thermal transfer resistance inside the color-changing warning layer, allowing heat to be transferred to the temperature-sensitive release irreversible color-developing microcapsules more quickly. In Comparative Example 3, after replacing the epoxy-containing ethylene-acrylate copolymer with an epoxy-free ethylene-acrylate copolymer, although it still exhibited some polymer compatibility, the color change response time increased to 88s, and the ΔE, ΔE retention rate, and interlayer peel strength after color change were all lower than those in Example 1. This indicates that the technical effect of this application does not simply come from the addition of a second ethylene copolymer. The epoxy-containing ethylene-acrylate copolymer has a better interfacial matching relationship with the silane-modified spherical alumina and the thermosensitive release irreversible color-developing microcapsules, which is beneficial to improving the dispersion stability of functional components and interfacial heat transfer.
[0054] Based on Examples 1-3, it is evident that the color-changing warning layer of this application can form a clear and well-retained color mark after overheating. Specifically, with the increase in the amount of thermosensitive release irreversible color-developing microcapsules, epoxy-containing ethylene-acrylate copolymer, and surface-modified spherical alumina, the overall thermal response speed and color recognition are improved; however, the high amount of functional components in Example 3 resulted in a decrease in tensile strength, indicating that excessively high inorganic filler and microcapsule content can have a certain impact on the mechanical properties of the composite layer.
[0055] Combining Examples 2, 4, and 5, Example 4, after using the surface-modified spherical alumina obtained in Example 5, showed that the color change response time was shortened to 55s, which is lower than 64s in Example 2 and 60s in Example 5, while maintaining a high interlayer peel strength. It can be seen that the surface-modified spherical alumina with the particle size of spherical alumina and an appropriate amount of γ-aminopropyltriethoxysilane used in Example 5 has the best performance.
[0056] Combining Examples 4, 6, and 7, the ΔE retention rates after 24 hours of cooling in Examples 6 and 7 reached 98.5% and 99.1%, respectively, which were higher than the 97.3% in Example 4. This indicates that appropriately increasing the raw materials for forming the microcapsule shell and adjusting the interfacial polymerization conditions is beneficial to improving the stability of the microcapsules at room temperature and their color retention ability after overheating. However, the color change response time in Example 7 increased to 70 seconds, indicating that excessively high microcapsule shell stability can also increase the core material release resistance, causing a decrease in response speed.
[0057] Combining Examples 6, 8, and 9, it can be seen that Example 8, which uses only linear low-density polyethylene, has a tensile strength of 20.4 MPa, but a decrease in interlayer peel strength; Example 9, which uses only low-density polyethylene, has a high interlayer peel strength, but a decrease in tensile strength to 15.7 MPa. Example 6, which uses a blend of linear low-density polyethylene and low-density polyethylene, achieves a good balance between tensile strength, interlayer bonding performance, and processing performance, indicating that the blend of the two is beneficial for balancing the strength and flexibility of the conductor insulation layer.
[0058] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A self-testing color-changing fault warning wire, characterized in that: It includes a conductive wire core and, from the inside out, a polyethylene insulation layer, a color-changing warning layer, and a transparent protective layer disposed on the outer side of the conductive wire core; the raw material of the color-changing warning layer includes the following components in parts by weight: 60-72 parts of ethylene-vinyl acetate copolymer, 5-10 parts of epoxy-containing ethylene-acrylate copolymer, 10-18 parts of thermosensitive release irreversible color-developing microcapsules, 5-20 parts of surface-modified spherical alumina, 0.2-0.5 parts of antioxidant, and 0.2-0.8 parts of lubricating and dispersing agent.
2. The self-testing color-changing fault warning wire according to claim 1, characterized in that: The preparation method of the thermosensitive release irreversible colorimetric microcapsules includes the following steps: An azo oil-soluble dye is added to n-hexadecane and stirred at 50–70°C until dissolved to obtain a dyed alkane indicator solution; the dyed alkane indicator solution, isocyanate prepolymer, and ethyl acetate are mixed to obtain an oil phase; Polyvinyl alcohol was added to deionized water to prepare an aqueous phase, and the oil phase was added to the aqueous phase. The mixture was emulsified at 3000-6000 rpm for 5-15 min to obtain an oil-in-water emulsion with an average droplet size of 5-15 μm. The oil-in-water emulsion is heated to 50-70°C, and water-soluble polyol and polyurethane reaction catalyst are added. The reaction is carried out at 300-600 rpm for 2-5 hours, so that the isocyanate prepolymer and water-soluble polyol polymerize at the oil-water interface and form a polyurethane-based shell. After the reaction was completed, the mixture was cooled, filtered, washed with deionized water, and vacuum dried at 40–60 °C to obtain thermosensitive release irreversible colorimetric microcapsules.
3. The self-testing color-changing fault warning wire according to claim 2, characterized in that: The weight ratio of the azo oil-soluble dye, n-hexadecane, isocyanate prepolymer, ethyl acetate, polyvinyl alcohol, deionized water, water-soluble polyol, and polyurethane reaction catalyst is (0.5-1.5):(25-35):(6-12):(10-20):(1-3):(80-120):(3-8):(0.02-0.08).
4. The self-testing color-changing fault warning wire according to claim 1, characterized in that: The method for preparing the surface-modified spherical alumina includes the following steps: Spherical alumina with a D50 of 0.5–2.5 μm was dried at 100–120 °C for 2–4 h and then added to an ethanol-water mixed solvent and ultrasonically dispersed for 20–40 min to obtain a spherical alumina dispersion. γ-aminopropyltriethoxysilane was added to an ethanol-water mixed solvent, and the pH was adjusted to 4.0-5.0 with acetic acid. The mixture was stirred and hydrolyzed at 20-30°C for 20-60 min to obtain a silane hydrolysate. The silane hydrolysate was added to the spherical alumina dispersion and reacted at 60–75°C and 300–500 rpm for 2–5 h to form a silane-modified layer on the surface of the spherical alumina with γ-aminopropyltriethoxysilane. After the reaction is complete, the mixture is filtered, washed 2-3 times with anhydrous ethanol, dried under vacuum at 70-80℃ for 4-12 hours, pulverized and depolymerized to obtain surface-modified spherical alumina.
5. The self-testing color-changing fault warning wire according to claim 4, characterized in that: The weight ratio of the spherical alumina to γ-aminopropyltriethoxysilane is 100:(1-3).
6. The self-testing color-changing fault warning wire according to claim 1, characterized in that: The raw materials for the polyethylene insulation layer include linear low-density polyethylene and low-density polyethylene, with a mass ratio of (65-80):(20-35).
7. The self-testing color-changing fault warning wire according to claim 1, characterized in that: The raw materials of the transparent protective layer include the following components in parts by weight: 65-80 parts of aliphatic polyurethane acrylate oligomer, 15-30 parts of acrylate reactive diluent, 1-4 parts of photoinitiator, 0.5-2 parts of ultraviolet absorber, 0.2-1 parts of hindered amine light stabilizer, and 0.3-1.5 parts of surface-modified nano silica.
8. A method for preparing a self-testing color-changing fault warning wire as described in any one of claims 1-7, characterized in that: Includes the following steps: S1. A polyethylene insulation layer is formed by extruding a conductive wire core, which is then cooled and shaped before being cross-linked by electron beam irradiation and cooled again. S2. Ethylene-vinyl acetate copolymer, epoxy-containing ethylene-acrylate copolymer, thermosensitive release irreversible color-developing microcapsules, surface-modified spherical alumina, antioxidant, lubricating and dispersing agent are mixed, replasticized and formed on the outside of polyethylene insulation layer to obtain color-changing warning layer. S3. A transparent protective layer is set outside the color-changing warning layer to obtain a self-testing color-changing fault warning wire.
9. The method for preparing a self-testing color-changing fault warning wire according to claim 8, characterized in that: In step S2, the highest processing temperature of the color-changing warning layer is at least 15°C lower than the thermal response temperature of the thermosensitive release irreversible color-developing microcapsule.